Reliability of the Minto model for target-controlled infusion of remifentanil during cardiac surgery with cardiopulmonary bypass. (August 2022) - Scherrer, Vincent; Lamoureux, Fabien; Chaventre, Céline; Thill, Caroline; Demailly, Zoe; Selim, Jean; Bauer, Fabrice; Imbert, Laurent; Wurtz, Véronique; Compère, Vincent; Clavier, Thomas; Besnier, Emmanuel
Abstract: Background: The Minto pharmacokinetic model is used for target-controlled infusion of remifentanil. The reliability of this model has never been evaluated during normothermic cardiac surgery with cardiopulmonary bypass (CPB). The aim of this study was to assess the predictive performance of the model during CPB to determine its reliability during cardiac surgery. Methods: This was a single-centre observational study. Arterial blood samples were drawn at five time points: T1, after tracheal intubation; T2, immediately before CPB; T3, 10 min after starting CPB; T4, 45 min after starting CPB; T5, 10 min after weaning off CPB. Prediction error (PE) and absolute prediction error (APE) were calculated for each sample and used to determine median prediction error (MDPE) and median absolute prediction error (MDAPE) per patient. Risk factors for APE >30% were assessed using multivariable analysis. Results are presented as medians with inter-quartile ranges. Results: Fifty-eight patients with 283 blood samples (110 during CPB) were included. In the pre-CPB period, MDPE and MDAPE were –17.3 [–32.9 to 2.3] and 24.6 [12–37.7]%, whereas during CPB, they were –1.8 [–15.6 to 11.1] and 14.0 [6.74–27.1]%, respectively. There was no statistically significant difference between measured and predicted remifentanil plasma concentrations during CPB. Age, preoperative albumin concentrations, temperature, and haemodilution were not independently associated with MDAPE >30%. Conclusions: The Minto model accurately predicts plasma remifentanil concentrations during cardiac surgery with CPB. Clinical trial registration: 2017-A03153-50.